Several conjectures about the existence of the ether - Cheng, Jinjun; Cheng, Dian (European Journal of Applied Sciences, 2021)
The "zero result" of Michelson Morley's experiment was not enough to deny the existence of a fifth element---ether, as conceived by Aristotle. Hubble's explanation of the Doppler effect of the systematic cosmic the red shift was incomplete and needed to be introduced into the ether.The physical significance of universal gravitation constant reveals the possibility of the existence of ether. After much thought and logical reasoning, there is good reason to think that the ether is negative energy, stream of consciousness, and space itself, it combines with photons to build elementary particles, elementary elements, everything in the universe, including ourselves. In addition, it is feasible to explain the causes of gravitation, electromagnetic force, strong force and weak force from the perspective of the ether, which seems to be easier for us to understand. The most tragic conclusion is that the universe was created out of nothing and will eventually return to nothing.